Deformation pattern of the NW terrane boundary of the Eastern Ghats Mobile Belt, India: a tectonic model and correlation with Antarctica - BISWAL, TK; BISWAL, B; MITRA, S; MOULIK, MR (Gondwana Research, 2002)
Thrusts interspersed with lateral ramp and wrench structures mark the join between Proterozoic Eastern Ghats Mobile Belt and Archaean cratons of the eastern India. The join, referred to as Terrane Boundary Shear Zone, exhibits an arcuate geometry at the NW margin of the Eastern Ghats where the mobile belt shows the presence of northwesterly verging nappes. Based on this, the area has been described to represent the salient part of a fold thrust belt. Juxtaposition of the granulites over the low grade craton is largely attributed to thrusting along the terrane boundary shear zone. As the folds are disoriented and the granulites are retrograded along the thrusts, the terrane boundary shear zone is interpreted to be a retrograde shear zone. The shear zone hosts a number of synkinematic alkali intrusive rocks that constrain the age of thrusting to 1.4 Ga. In the correlative framework of Gondwanaland the terrane boundary shear zone is very likely to be contiguous with the Rayner-Napier boundary of Antarctica.